Personality influences cognitive capacities in horses: synthesis of a series of experiments - Lansade, L.; Lévy, F.; Calandreau, L.; Fortin, M.; Vidament, M.; Valenchon, M. (DCA Report; Nr. 044, 2014)
Inter-individual variability in the expression of behaviour is a growing field of interest. A key factor to understand this variability is personality (temperament). A series of 7 experiments carried out on horses investigated whether certain types of personality promote cognitive abilities, especially instrumental learning performances. A model of personality has been developed in horse in our lab and permits to measure five independent dimensions with a series of behavioural tests. In these studies, stress, a key parameter that impacts learning performance, was manipulated. Low to moderate stress factors were used, corresponding to situations similar to those experienced by a horse at work (e.g. negative reinforcements or exposure to novel situations). The results show that if a horse was under stress at the time of learning, and if this stress was not caused by the learning situation itself (the horse was stressed prior to learning), the fearful horses were always disadvantaged (Valenchon et al., PLoS ONE, 8(4), 2013). Nevertheless, being fearful was not always detrimental. When no additional stress was added, fearful horses had superior working memory performance, suggesting a higher state of arousal (Valenchon et al., Anim. Behav. 1233-:1240, 2013). Furthermore, when the stress was induced by the task itself, for instance when using negative reinforcement, they also performed better (Lansade et al., Appl. Anim. Behav. Sci. 30:37, 2010). Finally, fearful horses have systematically been shown to be more resistant to extinction and are more prone to develop automatisms, suggesting a lower behavioural flexibility (Valenchon et al., Anim. Cogn., 1001: 1006, 2013; Lansade L., et al., PLoS ONE 8(6), 2013; Lansade et al.a,b, in preparation). The other dimensions, such as gregariousness, activity or sensory sensitivity have a weaker influence on learning performances. Overall, this work helps us to determine the advantages and drawbacks of each horse and to suggest suitable tailor-made training programs for each individual. LP: Among the different dimensions of personality, fearfulness seems to influence mostly the learning performances, but its influence is variable: generally positive in absence of stressor or when the cognitive task is the source of stress but negative in case of extrinsic stressors. We conclude that each kind of personality presents advantages or disadvantages depending on the learning conditions.